CSR INITIATIVES: THE PREDICTOR OF FINANCIAL PERFORMANCE IN ENERGY SECTOR - Haudi, .; Khairi, Aseh; Kenny, Kamal; Pathmathan, P. Ravindran (Archives of Business Research, 2020)
The purpose of this research was to investigate the relationship between Corporate Social Responsibility (CSR) and the financial performance for publicly-traded firms operating in the energy sector. The energy sector has a unique role to play in global CSR efforts because of the size of the firms within that industry, the impact on the environment, and the operational risks that come with energy production. Previous research has been conducted on the relationship between CSR engagement and financial performancein various contexts, but this research has shown mixed outcomes– in some cases there is a positive relationship between CSR and performance while in other studies the research is non-existent or marginal. Thus, the research question for this study addresses a significant gap in the understanding of this topic by exploring the relationship between CSR and firm performance in a contextualized setting of the energy sector. The dependent variable was a series of three financial metrics –returnon assets (ROA), return on equity (ROE), and EBITDA. This study looked into convenience sampling method and the population in this study was employees who were currently employed in an energy sector company in Malaysia.